Contributory factors for the functional independence of oldest old - Ribeiro,Dâmarys Kohlbeck de Melo Neu (2015)
OBJECTIVE To investigate the socioeconomic and clinical factors that contribute to the functional independence of the oldest old of a community. METHOD Cross-sectional quantitative study whose sample consisted of 214 elderly people registered in Basic Health Units. Data were collected through structured interviews and application of the Functional Independence Measure. We used descriptive statistics, and for association of the variables we used the Student t-test, ANOVA and Tukey's test for multiple comparisons. RESULTS The significant variables that contributed to the functional independence were remaining economically active, practicing physical and leisure activities, having a social life, eating fruits, vegetables and meat. The orientation to conduct these practices reduces the demand for care and help needed in everyday activities. CONCLUSION Maintaining independence is primordial to delay disability and presents itself as an excellent field of work for nursing.